The impact of chemotherapy on survival of patients with extremity and trunk wall soft tissue sarcoma: revisiting the results of the EORTC-STBSG 62931 randomised trial - Pasquali, Sandro; Kasper, Bernd (European journal of cancer, 2019)
Background - This study was aimed at determining whether patients with high-risk soft tissue sarcoma (STS), as identified using the nomogram Sarculator, benefitted from adjuvant chemotherapy in the EORTC-STBSG 62931 randomised controlled trial (RCT), which failed to detect an impact for adjuvant doxorubicin plus ifosfamide (Adj) over observation (Obs). - Methods - Patients with extremity and trunk wall STS in the EORTC-STBSG 62931 RCT were analysed (N = 290/351). Ten-year predicted probability of overall survival (pr-OS) was calculated using the prognostic nomogram Sarculator. Patients were grouped into three categories of predicted pr-OS: high (pr-OS>66%), intermediate (51<pr-OS≤66) and low (pr-OS≤51%). OS and disease-free survival (DFS) were calculated. - Results - Nomogram pr-OS was dispersed (median 72%, interquartile range 57-83%) and had prognostic value for OS and DFS (log-rank test: P < 0.001). One hundred seventy, 68 and 52 patients had high (58.6%, 90 Obs/80 Adj), intermediate (23.5%, 34 Obs/34 Adj) and low pr-OS (17.9%, 24 Obs/28 Adj), respectively. Adjuvant chemotherapy halved the risk of recurrence (hazard ratio [HR] = 0.46, 95% confidence interval [CI] 0.24-0.89) and death (HR = 0.46, 95% CI 0.23-0.94) in the low pr-OS category, while no effect was detected in intermediate and high pr-OS categories. To strengthen these findings, study participants with pr-OS<60% were combined (N = 80, 27.6%, 39 Obs/41 Adj), and a significant DFS (HR = 0.49, 95% CI 0.28-0.85) and OS (HR = 0.50, 95% CI 0.30-0.90) benefit was detected. - Conclusion - Patients of the EORTC-STBSG 62931 RCT with extremity and trunk wall STS and a low predicted pr-OS (high-risk patients) had better outcomes when treated with adjuvant chemotherapy. This may help reconcile the disparate results of clinical studies on adjuvant/neoadjuvant chemotherapy in STS.
Gesehen am 10.09.2019